First report of Mycobacterium virginiense-induced synovitis and tenosynovitis of flexor digitorum superficialis and profundus muscles in Japan. Issue 4 (April 2023) - Imoto, Waki; Matsumoto, Seishiro; Suzuki, Maya; Ban, Nozomi; Horikawa, Masayoshi; Mitani, Kei; Ogawa, Masashi; Kakuno, Shigeki; Shibata, Wataru; Niki, Makoto; Yamada, Koichi; Okada, Mitsuhiro; et al.
Abstract: Mycobacterium virginiense, a species of the Mycobacterium terrae complex, was first identified in 2016. Although M. virginiense has only been reported to cause tenosynovitis, there have been only a few reports. Moreover, there is no established standard treatment, and no cases of M. virginiense infection have been reported in Japan. A 70-year-old Japanese man with a history of hand injury and wound contamination was diagnosed with synovitis and tenosynovitis of the left flexor digitorum superficialis and profundus muscles. M. virginiense was detected in perisynovial reservoirs and surgically removed synovium and was identified by hsp65 and rpoB sequencing. Postoperative chemotherapy with clarithromycin, rifabutin, and ethambutol was administered. Infection with M. virginiense can occur in patients with synovitis and tenosynovitis who have experienced injury or wound contamination, requiring surgery and long-term treatment with multiple antibiotics.